Pengaruh Penambahan Tepung Daun Anting-Anting (Achalipha indica. l) Dalam Ransum Terhadap Konsumsi Dan Kecernaan Kalsium Dan Fosfor Ternak Babi - Dalle, Nautus Stivano; Nguru, David Agustinus; Berek, Christalia; Tukan, Hendrikus Demon; Nugraha, Elisabeth Yulia (Program Studi Peternakan Universitas Muslim Maros, 2024)
The purpose of this study was to find out how to use Earring Leaf Flour for basal diet for intake and digestibility of Calcium and Phosphor on pigs . The materials used were 12 male pigs of Landrace breeding which received 1-2 months with initial body weight of 30-50 kg, an average of 37.92 kg and (KV = 13,66%). This study used a randomized block design (RBD) with 4 preparations and 3 replications. The treatment tried was R0: 100% basal diet without leaves Earring (control), R1: 98% basal diet + 2% leaf Earring, R2: 96% basal diet + 4% leaf Earring, R3: basal diet 94% + 6% leaf earrings. The variables consumed were intake and digestibility of Calcium and Phosphor. The results showed that the study was not significant (P> 0.05) for intake and digestibility of calcium, and phosphor. Conclusion is the use of leaves Earrings up to 6% give a relatively similar response to the intake and digestibility of Calcium and Phosphor.